IDENTIFIKASI ARCA TOKOH BERKEPALA SINGA DI MUSEUM PENATARAN - Ashar Murdihastomo (Berkala Arkeologi, 2019)
The field study that was organized by the committee of Premodern Java Summer Programme in 2016 targeted several museums in East Java, especially in Mojokerto-Penataran area. That field study was intended to provide an understanding about the development of cultural arts during the end of Hindu-Buddhist period of Majapahit Kingdom. This paper is discussing about one of the objects that was being observed during that Summer Programme. The object of discussion is the lion-headed figure, stored in Museum Penataran. During the Summer Programme, some participants have predicted that the statue is Lord Vishnu in his Narasimha form. That prediction was mainly based on the statue's head which resemble a lion's head. Through several studies, such as the description of the statue, the literature study of iconography, and analysis about the special iconographic character, this paper concluded that this figure is a manifestation of Ganesha, named Simha-Ganapati. The worship of Simha-Ganapati has a purpose not only to bring strength and courage, but also to provide confidence in facing problems by destroying all forms of negative thoughts.